2020
DOI: 10.1002/cssc.202002240
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of Lignin into Monophenolics by Ferrous/Persulfate Reagent under Mild Conditions

Abstract: This study aimed to use a persulfate together with transition metal ions as the reagent to effectively depolymerize lignin into monophenolic compounds under mild conditions (ambient pressure, temperature <100 °C). The Box‐Behnken experimental design in combination with the response surface methodology was applied to obtain optimized reaction conditions. The results showed that this reagent could depolymerize up to 99 % of lignin dimers to mainly veratraldehyde. This reaction also successfully depolymerized ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…However, it should be noted that BC in the current research was shown to have a significant level of lignification or silicification of lignocellulosic biomass, resulting in a lower nutritional value. Silage fermentation or pretreatment of lignocellulose is therefore advised as a strategy to recover the nutritional value of BC ( 8 10 ), and it may be extended, at least qualitatively, to realistic feeding settings ( 6 ). Silage generated by the anticipated BC processing might potentially be used to mitigate some of the current environmental concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that BC in the current research was shown to have a significant level of lignification or silicification of lignocellulosic biomass, resulting in a lower nutritional value. Silage fermentation or pretreatment of lignocellulose is therefore advised as a strategy to recover the nutritional value of BC ( 8 10 ), and it may be extended, at least qualitatively, to realistic feeding settings ( 6 ). Silage generated by the anticipated BC processing might potentially be used to mitigate some of the current environmental concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of lignocellulose agricultural biomass or materials with inorganic salts prior to ensiling production has been identified in previous research as a viable strategy for recovering the nutritional content of highly lignified materials ( 8 10 ). Pretreatment with inorganic salts serves the overall purpose of increasing the efficiency with which hemicellulose and cellulose in biomass are hydrolyzed during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, with the other lignins, ALK conducted to lower conversions, never reaching 100 %. Alkaline pretreatment depolymerised lignin by cleaving the ether linkages and leaving instead available OH phenolic groups, which are the main cause for lignin re-condensation, reaching a very condensed and recalcitrant structure (Bao et al, 2020;Ma et al, 2018b). Analysis using ATR-FTIR confirmed the presence of the available OH groups by the presence of different bands.…”
Section: Lignin Conversionmentioning
confidence: 99%
“…Despite being less prevalent than methanol, the use of hexane in the current investigation could explain the successful recovery of complex plant matrices of S. androgynus from both polar and nonpolar substances. To determine phytochemicals from S. androgynus , however, the most recent review only included the use of organic solvents without mentioning the use of hexane [ 12 ]. Consequently, the current study may verify earlier research and provide additional evidence to support the concept of using alternative organic solvents for S. androgynus .…”
Section: Discussionmentioning
confidence: 99%